Preclinical toxicology and safety pharmacology of the first-in-class GADD45β/MKK7 inhibitor and clinical candidate, DTP3. (2019) - Tornatore, Laura; Capece, Daria; D'Andrea, Daniel; Begalli, Federica; Verzella, Daniela; Bennett, Jason; Acton, Gary; Campbell, Elizabeth A.; Kelly, James; Tarbit, Michael; Adams, Nigel; Bannoo, Selina; et al.
Graphical abstract: Highlights: DTP3 eliminates any viable MM cells in mice upon i.v. bolus administration. DTP3 exhibits highly favourable PK and ADME profiles, with long plasma half life. DTP3 had no adverse effect on vital organ systems in GLP safety pharmacology studies. DTP3 was tolerated in repeat-dose 28-day toxicity studies with wide exposure margins. Abstract: Aberrant NF-κB activity drives oncogenesis and cell survival in multiple myeloma (MM) and many other cancers. However, despite an aggressive effort by the pharmaceutical industry over the past 30 years, no specific IκBα kinase (IKK)β/NF-κB inhibitor has been clinically approved, due to the multiple dose-limiting toxicities of conventional NF-κB-targeting drugs. To overcome this barrier to therapeutic NF-κB inhibition, we developed the first-in-class growth arrest and DNA-damage-inducible (GADD45)β/mitogen-activated protein kinase kinase (MKK)7 inhibitor, DTP3, which targets an essential, cancer-selective cell-survival module downstream of the NF-κB pathway. As a result, DTP3 specifically kills MM cells, ex vivo and in vivo, ablating MM xenografts in mice, with no apparent adverse effects, nor evident toxicity to healthy cells. Here, we report the results from the preclinical regulatory pharmacodynamic (PD), safety pharmacology, pharmacokinetic (PK), and toxicology programmes of DTP3, leading to the approval for clinical trials in oncology. These results demonstrate that DTP3 combines on-target-selective pharmacology, therapeutic anticancer efficacy, favourable drug-like properties, long plasma half-life and good bioavailability, with no target-organs of toxicity and no adverse effects preclusive of its clinical development in oncology, upon daily repeat-dose administration in both rodent and non-rodent species. Our study underscores the clinical potential of DTP3 as a conceptually novel candidate therapeutic selectively blocking NF-κB survival signalling in MM and potentially other NF-κB-driven cancers.